CO2 Mitigation Measures of Power Sector and Its Integrated Optimization in China - Pan Dai; Guang Chen; Hao Zhou; Meirong Su; Haixia Bao (The Scientific World Journal)
Power sector is responsible for about 40% of the total CO2 emissions in the world and plays a leading role in climate change mitigation. In this study, measures that lower CO2 emissions from the supply side, demand side, and power grid are discussed, based on which, an integrated optimization model of CO2 mitigation (IOCM) is proposed. Virtual energy, referring to energy saving capacity in both demand side and the power grid, together with conventional energy in supply side, is unified planning for IOCM. Consequently, the optimal plan of energy distribution, considering both economic benefits and mitigation benefits, is figured out through the application of IOCM. The results indicate that development of demand side management (DSM) and smart grid can make great contributions to CO2 mitigation of power sector in China by reducing the CO2 emissions by 10.02% and 12.59%, respectively, in 2015, and in 2020.